Analysis of Stock Returns in Financial Restatements - Ordelia Septa Anindya; Lindrawati Lindrawati; Mudjilah Rahayu (Institute of Computer Science (IOCS), 2024)
When making an investment, investors of course first look at the condition of the company as reflected in the financial statements. Financial statements are prepared based on accounting standards where accounting standards follow existing developments so that changes occur. On the other hand, sometimes companies also prepare financial statements that do not reflect the condition of the company, this causes financial restatements to occur. The aim of this research is to analyze stock returns when a financial restatements occurs, namely before and after a financial restatements. The research object is a manufacturing company on the Indonesia Stock Exchange that carries out a financial restatements with an event window of three days before and three days after the announcement of the financial restatements. The research results show that there is no difference in stock returns before and after the announcement of the financial restatements, which shows that investors think that information on the causes of the financial restatements is not important information that can reduce or increase firm value so that it cannot influence investors' decisions in investing